TEACHERS' PERSPECTIVE ON THE IMPLEMENTATION OF COMMUNICATIVE APPROACH IN INDONESIAN CLASSROOMS - Yenny Rahmawati (IJEE (Indonesian Journal of English Education), 2018)
ABSTRACTCommunicative Approach (CA) is probably the most popular approach in the recent English language teaching (ELT) in Indonesia. The curriculum underpinning ELT in the country has changed several times, although in the last 35 years its basis has been revolving around the communicative approach. Despite the fact that the communicative curriculum has been implemented for a long time, some research studies (Dardjowidjojo, 2000; Musthafa, 2001) indicated that it has not brought significant improvements in the terms of learners’ outcome. The reason for this might be a number of the teachers appear to have developed some misconceptions of CLT. This study is, therefore, aimed at exploring EFL Indonesian teachers’ perspectives toward communicative approach in their classrooms. Six participants were involved in this study in which two participants were chosen from each level of education (primary, secondary and university levels). The study employed a qualitative design by using questionnaire and in-depth interviews as methods of data collection. The results indicated that the university teachers in this study tend to have a broader view of CLT, while a number of the school teachers appear to have developed some misconceptions of it, i.e. the “not” teaching grammar and the teaching “only” speaking. ABSTRAKPendekatan Komunikatif (CA) mungkin merupakan pendekatan yang paling populer dalam pengajaran bahasa Inggris (ELT) di Indonesia. Kurikulum yang mendasari ELT di Negara ini telah berubah beberapa kali, meskipun dalam 35 tahun terakhir pendekatan yang digunakan adalah pendekatan komunikatif. Terlepas dari kenyataan bahwa kurikulum komunikatif telah dilaksanakan dalam waktu yang lama, beberapa penelitian (Dardjowidjojo, 2000; Musthafa, 2001) menunjukkan bahwa pendekatan tersebut tidak membawa perbaikan yang signifikan bagi peserta didik. Alasan utama hal tersebut mungkin datang dari kesalahpahaman sejumlah guru terkait dengan CLT. Oleh karena itu, penelitian ini bertujuan untuk mengeksplorasi perspektif guru bahasa Inggrois terhadap pendekatan komunikatif di kelas mereka. Enam peserta terlibat dalam penelitian ini di mana dua peserta dipilih dari setiap jenjang pendidikan (tingkat dasar, menengah dan universitas). Penelitian ini menggunakan desain kualitatif dengan menggunakan kuesioner dan wawancara mendalam sebagai metode pengumpulan data. Hasil penelitian ini menunjukkan bahwa guru universitas dalam penelitian ini cenderung memiliki pandangan yang lebih luas tentang CLT, sementara sejumlah guru sekolah tampaknya telah mengembangkan beberapa kesalahpahaman diantaranya: "tidak" mengajar tata bahasa dan pengajaran "hanya" berbicara.  How to Cite: Rahmawati, Y.(2018). Teachers' Perspective on The Implementation of Communicative Approach in Indonesian Classrooms  . IJEE (Indonesian Journal of English Education), 5(1), 92-100. doi:10.15408/ijee.v5i1.9881